2002
DOI: 10.1159/000066521
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Alpha-<i>L</i>-Fucosidase Activity as a Prognostic Marker in Colorectal Cancer

Abstract: Objectives: The aim of this study was to examine the prognostic value of the preoperative serum α-L-fucosidase (AFU) activity in colorectal cancer and to assess whether it could add prognostic information that Dukes’ stages do not give. Methods: A postoperative follow-up of 137 colorectal cancer patients was performed, and survival analyses were carried out to evaluate the impact of AFU activity on disease-free survival. Dukes’ stage classification, preoperative serum carcinoembryonic antigen levels and six ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In CRC, increased activity of lysosomal exoglycosidases in serum and urine have been reported 26, 27. The activity of α‐L‐fucosidase in serum of patients with CRC was higher in patients with distant metastases than the activity in patients with lymph node metastases, with peritoneal metastases, or without metastasis 28. The balance of the fucosylation level is regulated by fucosyltransferases and fucosidase, and the low level of fucosylation revealed in our current study may be explained by the low expression of Fut8, as indicated in this study and by the activation of α‐L‐fucosidase in patients with CRC reported by other groups 25, 27…”
Section: Discussionmentioning
confidence: 95%
“…In CRC, increased activity of lysosomal exoglycosidases in serum and urine have been reported 26, 27. The activity of α‐L‐fucosidase in serum of patients with CRC was higher in patients with distant metastases than the activity in patients with lymph node metastases, with peritoneal metastases, or without metastasis 28. The balance of the fucosylation level is regulated by fucosyltransferases and fucosidase, and the low level of fucosylation revealed in our current study may be explained by the low expression of Fut8, as indicated in this study and by the activation of α‐L‐fucosidase in patients with CRC reported by other groups 25, 27…”
Section: Discussionmentioning
confidence: 95%
“…Another study also shows that the mean value of preoperative serum AFU activity was higher in colorectal cancer (CRC) patients with distant metastases than in those with lymph node or peritoneal metastases, or without metastasis. The measurement of preoperative serum AFU activity could serve to detect hidden metastases for CRC, even before surgical intervention (Ayude et al , 2003). Most of the CRC patients with distant metastasis, for example, hepatic metastasis have a higher serum AFU level probably due to a greater flux of the enzyme from the malignant liver tissue to extracellular fluid (Deugnier et al , 1984; Takahashi et al , 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Considerably higher sensitivity (60%) and specificity (94% for OPC; 89% for OC) of this enzyme were observed at a threshold >450.6 U/mL, which is suggestive of its usefulness for the detection of early changes during cancer development. Similarly, α‐L‐fucosidase in serum has been reported as a promising marker for the early detection and diagnosis of hepatocellular carcinoma 21, 24, 25, 40. Ayude et al demonstrated the diagnostic and prognostic utility of decreased serum α‐L‐fucosidase activity in patients with colorectal cancer 21, 24.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that alterations in serum and/or tissue α‐L‐fucosidase activity potentially may be useful in the diagnosis and management of cancer patients 5, 8, 21‐23. Serum α‐L‐fucosidase has been proposed as a marker for colorectal and hepatocellular carcinoma 21, 24, 25. Thus, earlier reports have encouraged interest in the use of serum fucosidase for the diagnosis of malignant diseases and as an indicator of tumor burden, metastasis, and response to anticancer treatments.…”
mentioning
confidence: 99%